Performance Comparison Between Ray Tracing Channel Model and IEEE 802.11ad Channel Model in 60 GHz Band - Dongbo Li; Zaixue Wei; Lin Sang (Dianxin kexue)
Now millimeter wave communication and large scale MIMO, 3D MIMO technology have become the research hotspot in the field of mobile communication. IEEE 802.11ad channel model, which is widely concerned in MIMO 3D scenario, is the empirical based on the measuring of the channel. However, ray tracing model belongs to the deterministic model. IEEE 802.11ad channel model and ray tracing channel model were introduced. Then the method of IEEE 802.11ad channel model and ray tracing channel model were simulated in the indoor scenes and the simulation data was counted that the comparison results of TOA, DS, AZIMUTH and AS were obtained. It turns out that both of the two channel models can be modeling for the indoor scenes correctly. But the two models also exist certain differences.